Effectiveness and cost of integrating a pragmatic pathway for prescribing liraglutide 3.0 mg in obesity services (STRIVE study): study protocol of an open-label, real-world, randomised, controlled trial. Issue 2 (13th February 2020) - Papamargaritis, Dimitris; Al-Najim, Werd; Lim, Jonathan; Crane, James; Lean, Mike; le Roux, Carel; McGowan, Barbara; O'Shea, Donal; Webb, David; Wilding, John; Davies, Melanie J
Abstract : Introduction: In the UK and Ireland, severe and complex obesity is managed in specialist weight management services (SWMS), which provide multicomponent lifestyle interventions to support weight loss, and use of medication if available. Liraglutide 3 mg (LIRA 3 mg) is an effective weight-loss medication, but weight loss in individual patients is variable, and its efficacy has not been assessed in SWMS. This study aims to investigate whether a targeted prescribing pathway for LIRA 3 mg with multiple prespecified stopping rules could help people with severe obesity and established complications achieve ≥15% weight loss in order to determine whether this could be considered a clinically effective and cost-effective strategy for managing severe and complex obesity in SWMS. Methods and analysis: In this 2-year, multicentre, open-label, real-world randomised controlled trial, 384 adults with severe and complex obesity (defined as body mass index ≥35 kg/m 2 plus either prediabetes, type 2 diabetes, hypertension or sleep apnoea) will be randomised via a 2:1 ratio to receive either standard SWMS care (n=128) or standard SWMS care plus a targeted prescribing pathway for LIRA 3 mg with prespecified stopping rules at 16, 32 and 52 weeks (n=256). The primary outcome is to compare the proportion of participants achieving a weight loss of ≥15% at 52 weeks with a targeted prescribing pathway versus standard care. Secondary outcomes include a comparison of (1) the weight loss maintenance at 104 weeks and (2) the budget impact and cost effectiveness between the two groups in a real-world setting. Ethics and dissemination: The Health Research Authority and the Medicines and Healthcare products Regulatory Authority in UK, the Health Products Regulatory Authority in Ireland, the North West Deanery Research Ethics Committee (UK) and the St Vincent's University Hospital European Research Ethics Committee (Ireland) have approved the study. The findings of the study will be published in peer-reviewed journals. Trial registration number: ClinicalTrials.gov—Identifier: NCT03036800 . European Clinical Trials Database—Identifier: EudraCT Number 2017-002998-20.